2020
DOI: 10.1002/chem.202002825
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Structural Complexity of Fluorinated Glucose Analogues: Insight into Lipophilicities and Solvation Effects

Abstract: In this work,w es ynthesized all mono-, di-, and trifluorinated glucopyranose analogues at positions C-2, C-3, C-4, and C-6. This systematic investigation allowed us to perform direct comparison of 19 Fr esonances of fluorinated glucose analoguesa nd also to determine their lipophilicities. Compounds with af luorine atom at C-6 are usually the most hydrophilic, whereas those with vicinal polyfluorinated motifs are the most lipophilic. Finally, the solvation energies of fluorinated glucosea naloguesw ere assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 81 publications
4
48
0
Order By: Relevance
“…1,2‐Dideoxy‐1,2‐difluorinated glucose was first reported as an improved ligand for glycogen phosphorylase, with an observed affinity that was higher than expected based on the cumulative increases afforded by the two mono‐deoxyfluoro derivatives [5a] . Subsequent studies have similarly reported on various di‐deoxyfluoro, [53f, 54] tri‐deoxyfluoro, [25a, 51, 53f, 55] and tetra‐deoxyfluoro [25a, 55b] glycomimetic derivatives with significantly enhanced affinities.…”
Section: Polar Hydrophobicitymentioning
confidence: 99%
See 1 more Smart Citation
“…1,2‐Dideoxy‐1,2‐difluorinated glucose was first reported as an improved ligand for glycogen phosphorylase, with an observed affinity that was higher than expected based on the cumulative increases afforded by the two mono‐deoxyfluoro derivatives [5a] . Subsequent studies have similarly reported on various di‐deoxyfluoro, [53f, 54] tri‐deoxyfluoro, [25a, 51, 53f, 55] and tetra‐deoxyfluoro [25a, 55b] glycomimetic derivatives with significantly enhanced affinities.…”
Section: Polar Hydrophobicitymentioning
confidence: 99%
“…In comparing tri‐deoxytrifluoro derivatives, compounds with all‐ cis configured F atoms were the least hydrophobic (Tal, −0.84), presumably a result of their larger molecular dipole [51] . Another recent study performed a comprehensive systematic comparison of mono‐, di‐, and tri‐deoxyfluorinated Glc derivatives, where it was observed that vicinal fluorination afforded the most lipophilic compounds, likely as a result of their greater reduction in polar surface area [53f] . Calculated free energies of solvation correlated well to the experimentally determined log P values.…”
Section: Polar Hydrophobicitymentioning
confidence: 99%
“…We first evaluated reduction conditions on a simpler difluorinated hexopyranose analogue. Thus, difluoroglucose 21, easily accessible in 3 steps from levoglucosan (1) [21], was subjected to lithium aluminium hydride (LiAlH 4 ) in THF (Scheme 1a) and difluoroglucitol 22 was isolated in 58% yield. The reaction was hardly reproducible because a thick gel was formed after neutralisation with an acidic resin, thus resulting in yield loss after a difficult filtration.…”
Section: Entrymentioning
confidence: 99%
“…Our group is interested in the synthesis, physical properties and biological activities of heavily fluorinated carbohydrates [19,[21][22][23][24][25]. With intermediates 2-5 in hand, we studied the reactivities of a small set of chirally distinct difluorinated 1,6-anhydro-β-ᴅ-hexopyranose analogues.…”
Section: Introductionmentioning
confidence: 99%
“… 22 24 Additionally, its particular physicochemical properties 25 introduce electronic and polar-hydrophobic effects. 26 Indeed, fluorine modulates the population of the conformational space 27 , 28 and lipophilicity of fluorine-containing carbohydrates. 29 Smart use of these features has already allowed development of new molecules that efficiently act as substrates 30 and inhibitors of glycosidases.…”
Section: Introductionmentioning
confidence: 99%